PENGARUH PENGGUNAAN VLOGGER ENDORSER PADA IKLAN DALAM MEMBENTUK NIAT BELI KONSUMEN - Ginsan Sarashadi; Amina Sukma Dewi (Jurnal Bisnis dan Manajemen (Journal of Business and Management), 2018)
This study aimed to determine the effect of  vlogger  in ads that can lead in to consumers' purchasing intentions. Sample of this study was taken by purposive sampling method, with 206 respondents. Criteria of the samples in this study are women who lived in Solo, aged 18 years or older, knowing or ever watch vlogs, and have never bought beauty products wich has been advertised by the vlogger. The results using Structural Equation Model Smart PLS 2 shows that vlogger's attractiveness, vlogger's trustworthiness and expertise of a vlogger have a positive effect on attitudes toward advertising. The result also shows that the attitudes toward advertising also affect positively on consumer purchase intentions. According to this research, marketer should hire a vlogger endorser in order to promoting their product, because it is a pretty effective way for marketers to capture the potential market for their product. Limitations in this study are the setting of places in this study are only focused  on the Region of Solo  and the number of samples are  only 206 people, making it difficult to generalize the results of this study.